Multidisciplinary approach to a patient with agenesis of the corpus callosum. - Matheus, Cirit (2021)
The four-year clinical evolution of a patient seen for the first time at the age of 17 days, when he was admitted to the emergency room due to seizures and malnutrition, is described. During this hospitalization, neuroimaging tests led to the diagnosis of Agenesis of the corpus callosum (ACC), a malformation that can occur in isolation or in association with other systemic or central nervous system conditions. ACC is considered one of the most frequent brain malformations, with an estimated prevalence of 1 in 4000 live births. The main theoretical and clinical contributions about the disease are reviewed. It is concluded that the importance of the case lies in the fact that the interdisciplinary strategies used in the treatment of ACC patients have generated significant changes in their clinical evolution. As well, the commitment and participation of the parents in the application of palliative care is of significant importance.